2020
DOI: 10.1007/s12325-020-01503-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of a Non-Alcoholic Fatty Liver Disease Population Across the Fibrosis Spectrum Measured by Magnetic Resonance Elastography: Analysis of Screening Data

Abstract: Introduction: Non-alcoholic fatty liver disease (NAFLD), one of the most common liver diseases, is associated with liver-related complications and metabolic comorbidities. The phenotype is wide, ranging from simple steatosis to non-alcoholic steatohepatitis with advanced fibrosis. In this analysis of a phase 1 trial, clinical characteristics of screened subjects with NAFLD were studied according to the extent of fibrosis assessed using magnetic resonance elastography (MRE). Methods: One hundred ninety-four sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…MRE and MRI‐PDFF assessments were performed at baseline and every 24 weeks after randomisation to evaluate liver stiffness and liver steatosis, respectively. MRI assessments were conducted as described previously 30 . MRI/MRE assessments were conducted using a Siemens 1.5T MRI scanner.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MRE and MRI‐PDFF assessments were performed at baseline and every 24 weeks after randomisation to evaluate liver stiffness and liver steatosis, respectively. MRI assessments were conducted as described previously 30 . MRI/MRE assessments were conducted using a Siemens 1.5T MRI scanner.…”
Section: Methodsmentioning
confidence: 99%
“…MRI assessments were conducted as described previously. 30 MRI/MRE assessments were conducted using a Siemens 1.5T MRI scanner. MRI‐PDFF was performed using a 3D 6‐echo gradient echo sequence covering the entire liver, and quantitative PDFF maps were reconstructed.…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, about 25% of the global population suffered from nonalcoholic fatty liver disease (NAFLD), which is currently one of the most common liver diseases except viral hepatitis. In addition to increasing the risk of hypertension and hyperlipidemia, the probability of fatty liver patients’ concurrent cirrhosis and liver cancer is 150 times that of healthy people. Atorvastatin is a commonly used lipid-regulating drug in clinical practice, affecting the synthesis of cholesterol and working for NAFLD. , On the premise that the effect of atorvastatin on the luminescence of CDs is negligible (Figure S20), the CDs were used as a beacon to investigate the effect of atorvastatin on the uptake of lipid in hepatocytes and to investigate the role of the probe in the screening and efficacy evaluation of lipid-regulating drugs. First, the LDs were labeled by CDs to observe the status under normal physiological conditions (Figure E) and then changed to high-fat medium and cultured for another 24 h. It is observed that the brightness and number of LDs increased significantly (Figure F).…”
Section: Resultsmentioning
confidence: 99%
“…Other tissues of interests for investigating the extent and damage of diabetes are the liver and the pancreas. Magnetic resonance elastography (MRE) has been used for assessing the stage and severity of liver fibrosis in diabetic patients via measuring liver stiffness [329,330]. [331].…”
Section: Imaging Fibrosis In Diabetesmentioning
confidence: 99%